1994
DOI: 10.1002/job.4030150606
|View full text |Cite
|
Sign up to set email alerts
|

Presence of drug screening and employee assistance programs: Exclusive and inclusive human resource management practices

Abstract: Drug screening and employee assistance programs (EAPs) are human resource management practices for addressing substance abuse among employees. The two practices reflect different human resource management strategies and lead to different outcomes for employees and applicants. Drug screening is designed to exclude drug users from the workplace whereas EAPs offer them ‘rehabilitation’. Characteristics of worksites and their surrounding labor market may influence the presence or absence of these personnel practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Several prior studies have documented higher substance abuse testing activities in industries with higher occupational safety concerns and greater degree of regulations such as mining, manufacturing, transportation and utilities (Bennett, et al, 1994; Hartwell, Steele, French, & Rodman, 1996; Jacobson, 2003; Lu & Kleiner, 2004). Our study supplements these results with the finding that employers in this combined industry sector with a greater focus on workplace safety were more likely to provide enrollees with a generous EAP benefit, both in number of sessions and by less restrictive session limits.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior studies have documented higher substance abuse testing activities in industries with higher occupational safety concerns and greater degree of regulations such as mining, manufacturing, transportation and utilities (Bennett, et al, 1994; Hartwell, Steele, French, & Rodman, 1996; Jacobson, 2003; Lu & Kleiner, 2004). Our study supplements these results with the finding that employers in this combined industry sector with a greater focus on workplace safety were more likely to provide enrollees with a generous EAP benefit, both in number of sessions and by less restrictive session limits.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The provision of employee benefits and workplace practices exhibit distinct differences across workplaces and are reflective of varied strategies, organizational cultures and human resource practices (Bennett, Blum, & Roman, 1994). Despite the growth in both public-sector provision of healthcare coverage and a rise in the percentage of the population uninsured, 60% of the non-elderly US population continues to be enrolled in employer-paid insurance plans (DeNavas-Walt, Proctor, & Smith, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it stands to reason that larger organizations may be more likely than smaller organizations to choose a rehabilitative strategy of internalization when dealing with the drug-using employee. In addition, JOURNAL OF DRUG ISSUES previous research has demonstrated that larger organizations are more likely to have resources that can address employees' problems (Bennett, Blum, & Roman, 1994;Milne & Blum, 1998). The greater resources of larger organizations may mean that these organizations have the ability to invest more in helping an employee who tests positive for drug use.…”
Section: The Role Of Organizational Structurementioning
confidence: 99%
“…While previous studies have indicated that workplace characteristics affect the choices employers make to adopt human resource practices such as performance appraisal (Cleveland, Murphy & Williams, 1989), employee training and development (Jackson, Schuler & Rivero, 1989), drug screening (Bennett, Blum & Roman, 1994), and insurance coverage of the costs of alcoholism treatment (Fennell, 1984), there has been little empirical research on the influence these organizational characteristics may have on the presence of health care cost containment practices. Much of the literature on employer health care insurance provision and cost containment practices has been largely atheoretical and descriptive in nature.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…On the basis of previous research (Bennett et al, 1994;Jackson et al, 1989;Feldman et al, 1991), there is reason to anticipate differences in the pattern of benefits offered by service and non-service firms, suggesting that service firms may have different strategies in controlling health care costs and different constituencies to consider. Research has further indicated that service lirrns tend to have higher proportions of managers, and employ more skilled workers and more white collar workers, than do non-service employers (Falk & Lyson, 1988).…”
Section: Hlbmentioning
confidence: 99%